The Effect of Ethanol on Brake Torque, Brake Specific Fuel Consumption, Smoke Opacity, and Exhaust Gas Temperature of Diesel Engine 4JB1 Fueled by Diesel-Jatropha Oil - Syarifudin Syarifudin; Faqih Fatkhurrozak; Firman Lukman Sanjaya; Eflita Yohana; Syaiful Syaiful; Agus Wibowo (Automotive Experiences, 2022)
The growth of diesel vehicles has consequences for the consumption of diesel oil. Therefore, using Jatropha as an alternative fuel reduces dependence on diesel oil and it does not interfere with food availability. However, the high viscosity of jatropha oil makes the fuel pump work harder. In addition, the low calorific value reduces the quality of the fuel which creates unique problems. Ethanol, with its low viscosity and high oxygen content, is expected to be effective in reducing jatropha problems for diesel engines. Therefore, this study aims to evaluate the addition of ethanol to the brake torque, brake-specific fuel consumption, exhaust gas temperature, and smoke opacity. The 4JB1 diesel engine with an EGR was tested on a 10% (DJ10) and 20% (DJ20) diesel-jatropha mixture. The experimental results showed that brake torque increased by 1.51% in the DJ10 application, brake specific fuel consumption decreased by 7.05%, exhaust gas temperature decreased by 0.67%, and smoke opacity increased by 25.91%. While in the DJ20 application, brake torque increased by 3.19%, brake-specific fuel consumption decreased by 30.08%, exhaust gas temperature decreased by 0.67%, and smoke opacity increased by 69.03%.